جهود الأمن الوطني الجزائري في مواجهة تهديدات الامن السيبيراني - غدير، عبد القادر; قريشة، خالد (University Of Eloued جامعة الوادي, 2024)
This study addresses the issue of the Algerian state’s efforts to confront cybersecurity threats through the programs and mechanisms developed by the Algerian National Security to confront these threats. This study will address the efforts made by the Algerian security authorities to confront cyberthreats by creating a security system that is compatible with the transformations Global geostrategy: With the increasing volume of cyber threats that affect the information security of countries, leading to the breach of their economic, political and strategic security, it has become necessary to develop an Algerian defensive security strategy and adapt it according to future requirements to confront threats according to their degree of seriousness, while anticipating what the actors who pose a threat will do. Possible, and dealing with these threats according to the logic of expectation
مداخلة
Keywords: الأمن السيبيراني; الأمن الوطني الجزائري; التهديدات السيبيرانية; الأمن السيبيراني الاقتصادي والسياسي والاستراتيجي; cybersecurity; Algerian National Security; cyber threats; Economic; political and strategic cybersecurity